Luminescence Quenching and Enhancement by Adsorbed Metal Ions with Ruthenium Diimine Complexes Immobilized on Silica Polyamine Composites - Rosenberg, Edward (Macromol Symp, 2016)
Luminescent ruthenium diimine complexes have been covalently bound to the surface of a silica polyamine composite (SPC) using peptide coupling agents. The loading of the complexes using this route is quite low (~0.01–0.04 mmol/g) leaving sufficient surface amines to coordinate added metal ions. When the composite particles containing the Ru complexes are exposed to solutions of Cu(2+), Ni(2+) or Zn(2+), luminescence is quenched with efficiencies that follow concentration dependence and the relative binding affinities of the ions. When heavy metal ions such as mercury or lead are adsorbed onto the same surface, luminescence is enhanced by a factor of ~3.5. When the complexes are exposed to these metals in solution, no quenching or enhancement is observed. Both phenomena were shown to be the result of adsorption of the cations onto the polyamine surface by using the Stern-Volmer relationship. The mechanism of both quenching and enhancement is discussed and the options for further development of this novel metal sensing technique are presented.